2022
DOI: 10.1002/cpp.2757
|View full text |Cite
|
Sign up to set email alerts
|

Desire thinking as an underlying mechanism in alcohol use disorder and nicotine dependence

Abstract: Desire thinking is an emerging construct in the addictive behaviours literature. No research, to date, has investigated its contribution to problematic alcohol use and nicotine dependence in patient samples when accounting for established predictors of addictive behaviours. The present study sought to clarify, in patient samples, the relative contribution of desire thinking in the associations between negative affect, impulsivity and thought suppression on the one hand and craving, problematic alcohol use and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…These results are consistent with earlier studies, which reported an association between desire thinking and addictive behaviors ( Caselli & Spada, 2015 ), including problematic SNS use ( Khosravaniet al, 2022 , Solemet al, 2021 ), problematic Facebook use ( Marino et al, 2019 ), problematic internet use ( Spada et al, 2014 ), problematic internet pornography use ( Allenet al, 2017 , Brandtner and Brand, 2021 ), and Internet Gaming Disorder ( Aydınet al, 2022 , Brandtneret al, 2020 , Brandtner and Brand, 2021 , Dragan and Grajewski, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with earlier studies, which reported an association between desire thinking and addictive behaviors ( Caselli & Spada, 2015 ), including problematic SNS use ( Khosravaniet al, 2022 , Solemet al, 2021 ), problematic Facebook use ( Marino et al, 2019 ), problematic internet use ( Spada et al, 2014 ), problematic internet pornography use ( Allenet al, 2017 , Brandtner and Brand, 2021 ), and Internet Gaming Disorder ( Aydınet al, 2022 , Brandtneret al, 2020 , Brandtner and Brand, 2021 , Dragan and Grajewski, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…We acknowledge that the potential relationship between desire thinking, negative affect, and impulsivity may blur the lines of the prominence of desire thinking in predicting craving and addictive patterns of behavior. However, desire thinking was found to play an independent role in problematic social media use ( Sharifi et al, 2022 ), Alcohol Use Disorder, and nicotine dependence ( Khosravaniet al, 2022 ), regardless of negative affect and impulsivity. Additionally, the existing literature has shown that boredom may be a potential predictor of problematic SNS use ( Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding various challenges and stressors among homeless individuals that increase tobacco use as a coping mechanism [30], some factors, such as high-stress levels, social isolation, and limited resources, contribute to higher tobacco use rates in low-income populations [30]. Hence, treating nicotine dependence is essential for the well-being of homeless individuals with AUDs [31]. Integrated treatment approaches by targeting both alcohol and nicotine dependence, as well as addressing the underlying causes of homelessness, could improve outcomes [31].…”
Section: The Cut Down Annoyed Guilty Eye-opener (Cage) Questionnairementioning
confidence: 99%
“…Hence, treating nicotine dependence is essential for the well-being of homeless individuals with AUDs [31]. Integrated treatment approaches by targeting both alcohol and nicotine dependence, as well as addressing the underlying causes of homelessness, could improve outcomes [31]. Indeed, providing resources and support to reduce tobacco-related health risks is crucial for this vulnerable population [30,31].…”
Section: The Cut Down Annoyed Guilty Eye-opener (Cage) Questionnairementioning
confidence: 99%